FINANCIAL PERFORMANCE ANALYSIS FOR RETURN ON ASSETS WITH A MULTIPLE LINIER REGRESSION APPROACH - Hendra H Dukalang (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2020)
This study aims to model the factors that affect the financial performance of Bank Muammalat, including Capital Adequacy Ratio (CAR), Earning Asset Quality (KAP), Operational Expenses to Operating Income (BOPO), and Financing to Deposit Ratio (FDR) to Return on Assets. (ROA) This research uses secondary data taken based on time series. The analysis technique in this study uses multiple linear regression using SPSS software version 20 and Microsoft Office Excel 2010. The results of this study indicate that partially the CAR and KAP partially do not have a significant effect on Return On. Assets, while Operational Expenses to BOPO and FDR partially have a significant effect on Return on Assets. Simultaneously, these four variables have a significant effect on Return on Assets at PT Bank Muamalat Indonesia. Based on the results of the Determination Coefficient test, the value of Adjusted R Square (R2) is 99.00%, this means that the amount of Return on Assets can be influenced and explained by the variables CAR, KAP, BOPO, and FDR, while the remaining 1% is explained by variables not examined in this study.